The rationale of using angiotensin receptor blocker instead of pulmonary vasodilators to treat pulmonary hypertension in bronchopulmonary dysplasia: a case report and literature review - Lindberg, Lars (Frontiers in Pediatrics, 2025)
This case report highlights the challenges in treating bronchopulmonary dysplasia (BPD) in a premature infant with severe pulmonary hypertension, recurrent pulmonary hypertensive crises, and the need of 100% oxygen to achieve acceptable arterial oxygen saturations. Key factors in the infant's improvement involved switching from pulmonary vasodilation to systemic afterload reduction using losartan, an angiotensin II type 1 receptor blocker. This alteration in treatment strategy led to a pronounced and prompt decrease in pulmonary arterial pressure, reduced oxygen dependency and resolution of pulmonary hypertensive crises. The infant's remarkable clinical response suggests that the pulmonary hypertension in BPD may have a pulmonary post-capillary cause, possibly driven by angiotensin II. A literature review corroborates this revision of the current understanding of the pathophysiologic mechanism involved in BPD and suggests that therapies targeting the renin-angiotensin-aldosterone system rather than pulmonary vasodilation may be an effective treatment strategy.